Self‐cleaning Bombyx mori silk: room‐temperature preparation of anatase nano‐TiO2 by the sol–gel method and its application. (18th April 2014) - Zheng, Chenghui; Qi, Zhenming; Shen, Wenchao; Chen, Guoqiang
<x xml:space="preserve">Abstract</x> The aim of this work was to obtain anatase nano‐TiO2 by the sol–gel method at room temperature and to achieve self‐cleaning Bombyx mori silk fabrics. Nano‐TiO2 sols based on an aqueous system and an ethanol system were prepared separately by the sol–gel method using tetrabutyl orthotitanate as a precursor at room temperature. Particle size analyses showed that nano‐TiO2 particles in an aqueous system were much bigger and more variant than those in ethanol. X‐ray diffraction patterns revealed a pure anatase phase of nano‐TiO2 in an aqueous system. Crystalline transformation of TiO2 from anatase to rutile by photoradiation at ambient temperature was also proved. Thermogravimetric and differential scanning calorimetric analyses confirmed the phase transformation of nano‐TiO2. A scanning electron microscope equipped with an energy‐dispersive spectrometer was used to investigate the surface morphology and elements of Bombyx mori silk fabrics. The contact angles with water, the kinetics of photocatalytic degradation of Methylene Blue, and decontamination of red‐wine‐stained fabrics under ultraviolet radiation demonstrated that the fabrics had good self‐cleaning properties and photoinduced hydrophilicity.